PANDANGAN MUQĀTIL BIN SULAIMĀN AL-BALKHĪ (W. 150 H/767 M) TENTANG MUḤKAMĀT DAN MUTASHĀBIHĀT - Siti Amilatus Sholihah; Afrohul Banat (AL ITQAN: Jurnal Studi Al-Qur'an, 2017)
This article focuses on muḥkamāt and mutashābihāt from the perspective of MuqÄtil bin SulaimÄn. Study on muḥkamāt and mutashābihāt is of importance because the implications which these topics has are not only on the aspects of linguistics, buat also on those of theology and laws. The choice of MuqÄtil as the case study is based on the fact that he is the first mufassir who succeeded in publishing the exegesis book of complete thirty juz of the Quran. The problem formulation of this article is the position of MuqÄtil's idea on muḥkamāt and mutashābihāt  in the battle of theological-political discourses in his era. To answer this, the writer makes use of the history of the schools of thought as the tool of analysis. The conclusion gained from this study is that Muqatil himself basically is not consistent in muḥkamāt and mutashābihāt. On one side, he tends to be in safe position, and on the other side is sometimes considered as mujassimah by many scholars. Such inconsistency is normal along with the growing reality surrounding Muqatil himself and his own realm of thought.